Medical ethics and internal medicine - Maiorano, Giuseppe; Albano, Ottavio (Medicina e Morale, 1984)
Recent scientific and technological advances in medicine have raised a number of ethical and regulatory problems, to which medicine alone can no longer provide adequate answers. Bioethics, as an interdisciplinary reflection, essentially deals with the ethical and regulatory aspects posed by biology in general; medical ethics, on the other hand, deals with the more specific aspects of medicine.